The Implication Of The Scripture Genesis 11:1-9 In Multicultural Context Of Indonesia - Merilyn Merilyn (Satya Widya: Jurnal Studi Agama, 2020)
The biblical text contains many narratives that are relevant to human problems today. This paper is an exegetical study of the text of Genesis 11: 1-9 which contains a narrative about human arrogance and fear over their abilities and towards human differences. But God broke the arrogance and fear of humans by disrupting their communication. God's purpose is to show that diversity is a necessity. This research was conducted with an exegetical method by combining narrative and semiotic criticism approaches. This critical approach describes who the characters are and their role in the narrative, the narrative plot, the meaning obtained through words/symbols and time, as well as what narrative is discussed and the author's perspective. The purpose of this paper is to deconstruct and find the hidden meaning of the text as well as reconstruct it and discover the implications of the text in multicultural society in Indonesia today. And the conclusion reached is that the biblical narrative is always relevant to human life today. In the context of this paper, the narrative in the Tower of Babel story stresses that God values ​​diversity and that diversity must be lived by everyone.